Α‐Tricalcium phosphate cements modified with β‐dicalcium silicate and tricalcium aluminate: Physicochemical characterization, in vitro bioactivity and cytotoxicity. Issue 1 (25th April 2014) - Correa, Daniel; Almirall, Amisel; Carrodeguas, Raúl García; dos Santos, Luis Alberto; De Aza, Antonio H.; Parra, Juan; Morejón, Lizette; Delgado, José Angel
Abstract Biocompatibility, injectability and in situ self‐setting are characteristics of calcium phosphate cements which make them promising materials for a wide range of clinical applications in traumatology and maxillo‐facial surgery. One of the main disadvantages is their relatively low strength which restricts their use to nonload‐bearing applications. α‐Tricalcium phosphate (α‐C3P) cement sets into calcium‐deficient hydroxyapatite (CDHA), which is biocompatible and plays an essential role in the formation, growth and maintenance of tissue‐biomaterial interface. β‐Dicalcium silicate (β‐C2S) and tricalcium aluminate (C3A) are Portland cement components, these compounds react with water to form hydrated phases that enhance mechanical strength of the end products. In this study, setting time, compressive strength (CS) and in vitro bioactivity and biocompatibility were evaluated to determine the influence of addition of β‐C2S and C3A to α‐C3P‐based cement. X‐ray diffraction and scanning electron microscopy were used to investigate phase composition and morphological changes in cement samples. Addition of C3A resulted in cements having suitable setting times, but low CS, only partial conversion into CDHA and cytotoxicity. However, addition of β‐C2S delayed the setting times but promoted total conversion into CDHA by soaking in simulated body fluid and strengthened the set cement over the limit strength of cancellous bone. The best properties were obtained for cement added with 10 wt % of β‐C2S, which showed in vitro bioactivity and cytocompatibility, making it a suitable candidate as bone substitute. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 72–83, 2015.